Nanogels as target drug delivery systems in cancer therapy: A review of the last decade - Attama, Anthony A.; Nnamani, Petra O.; Onokala, Ozioma B.; Ugwu, Agatha A.; Onugwu, Adaeze L. (Frontiers in Pharmacology, 2022)
Cancer is an important cause of morbidity and mortality worldwide, irrespective of the level of human development. Globally, it was estimated that there were 19.3 million new cases of cancer and almost 10 million deaths from cancer in 2020. The importance of prevention, early detection as well as effective cancer therapies cannot be over-emphasized. One of the important strategies in cancer therapy is targeted drug delivery to the specific tumour sites. Nanogels are among the several drug delivery systems (DDS) being explored as potential candidates for targeted drug delivery in cancer therapy. Nanogels, which are new generation, versatile DDS with the possession of dual characteristics of hydrogels and nanoparticles have shown great potential as targeted DDS in cancer therapy. Nanogels are hydrogels with a three-dimensional (3D) tuneable porous structure and a particle size in the nanometre range, from 20 to 250 nm. They have been visualized as ideal DDS with enormous drug loading capacity, and high stability. Nanogels can be modified to achieve active targeting and enhance drug accumulation in disease sites. They can be designed to be stimulus-responsive, and react to internal or external stimuli such as pH, temperature, light, redox, thus resulting in the controlled release of loaded drug. This prevents drug accumulation in non-target tissues and minimizes the side effects of the drug. Drugs with severe adverse effects, short circulation half-life, and easy degradability by enzymes, such as anti-cancer drugs, and proteins, are suitable for delivery by chemically cross-linked or physically assembled nanogel systems. This systematic review summarizes the evolution of nanogels for targeted drug delivery for cancer therapy over the last decade. On-going clinical trials and recent applications of nanogels as targeted DDS for cancer therapy will be discussed in detail. The review will be concluded with discussions on safety and regulatory considerations as well as future research prospects of nanogel-targeted drug delivery for cancer therapy.